ANALISIS SANKSI EKONOMI OLEH AMERIKA SERIKAT TERHADAP KUBA PASCA-REVOLUSI HINGGA AKHIR PERANG DINGIN (1960-1991): PERSPEKTIF CARL SCHMITT TENTANG STATE OF EXCEPTION - Suwarto, Nicholas Peter (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This research is motivated by the revolution initiated when Fidel Castro led resistance against the government ofPresident Fulgencio Batista, who had previously staged a coup against the general election in 1952. Following therevolution in Cuba, Fidel Castro, as the new head of government, transformed Cuba's system of governance to bebased on the principles of communism. Observing the impact of the adoption of communism under Fidel Castro'sadministration, the United States decided to impose economic sanctions on Cuba. The purpose of this study is toexplore how the imposition of economic sanctions on Cuba can be understood through the perspective of CarlSchmitt's “State of Exception.” To address this, the author employs Carl Schmitt’s concept of the "State ofException," which explains how sovereign power possesses the authority to suspend the legal system. Thus, thispower can declare a "State of Exception" if a country faces an existential threat to its integrity. A qualitativeapproach and descriptive method form the basis for data collection and analysis. The sanctions imposed by theUnited States, from the Eisenhower administration to the Reagan administration, have had various implications,encompassing economic, tourism, and health sectors. This study finds that, through Carl Schmitt's perspective of thestate of exception, the economic sanctions against Cuba can be understood as a sovereign act taken by the UnitedStates based on a political decision to address what it perceives as a threat to its national interests. Keywords: Republic of Cuba, United States Embargo, Carl Schmitt, State of Exception